PENGARUH PERENCANAAN KARIR DAN SISTEM KOMPENSASI TERHADAP KARIR PLATEAU DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING (STUDI DI AKADEMI KEPOLISIAN SEMARANG) - Suramta, Suramta (Students Journal of Economic and Management, 2012)
This study aims to examine the relationship of career planning dam compensation system for career plateau with job satisfaction as an intervening variable, a study at the Police Academy in Semarang. The sample in this study was Police Academy personnel. Sampling using simple random sampling. Questionnaire data were distributed and analyzed as much as 290. Hypothesis test results show that the overall hypothesis tested in this study received. While job satisfaction variables does not give effect to all variables intervening. Keywords: Career Planning, Compensation System, Job Satisfaction, Career Plateau.